Wsparcie polskiego rolnictwa i obszarów wiejskich w ramach wspólnej polityki rolnej po akcesji z Unią Europejską - Bartkiewicz, Halina (Support to Polish Agriculture and Rural Areas within Common Agricultural Policy after the Accession with the European Union, 2005)
After Polish accession to the European Union, Polish agriculture and rural areas were comprised by mechanisms of the Common Agricultural Policy (CAP). Polish agriculture as a part of European Union's agriculture will get access to many aid instruments resulted from the CAP. Thanks to the CAP there is possibility to use the Union's funds appropriated for an agricultural development. The article takes issues of some forms of financial support for agriculture and rural areas. It also presents the analysis of its influence on the growth of farms' competitive power and their income.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 38-44